Ukraine in crisis: Challenges of developing a new political culture - Steffen Halling; Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2014)
Ukraine is currently experiencing its worst crisis since obtaining independence in 1991. Violent escalation in Kyiv costing dozens of lives, separatist endeavours in Crimea and instability in the eastern provinces result not only from Russia's irresponsible great-power politics, but also from an elite prioritising its own self-interest. Viktor Yanukovych's corrupt and increasingly authoritarian regime was merely the most extreme expression yet of a political culture dedicated to serving special interests with no heed to good governance. With popular hopes of meaningful political change already dashed once after the Orange Revolution, how Ukrainian politicians handle their power now and in the future will be absolutely crucial. (SWP Comments)
Keywords: 320